Morphological synthesis and environmental application of ZSM-5 zeolite crystals from combined low-water and fluoride syntheses routes - Amosa, Mutiu K.; Al-Khatib, Ma'an Fahmi Rashid; Jami, Mohammed Saedi; Jimat, Dzun Noraini; Uthman, Owolabi R.; Muyibi, Suleyman Aremu (AENSI Publications, 2014)
ZSM-5 crystals have been morphologically prepared through the combination of Fluoride and Low-Water Synthesis Routes. This was done in order to bring about larger zeolite crystals with high Si/Al ratio and surface area suitable for environmental applications. The zeolite was analyzed to have crystal size between 200 – 218μm with a micropore volume of 0.79cm3/g. It was also found to possess a Si/Al ratio (SAR) of 194.4 with good adsorption and catalytic prowess when analyzed by SEM and XRD. The prepared zeolite was employed in the petroleum refinery wastewater treatment to evaluate its organic and inorganic removal efficacies as evident from the Chemical Oxygen Demand (COD) and Iron (Fe) contents adsorption where it exhibited 99% and 98% efficiency removal respectively.